2005
DOI: 10.4161/cbt.4.11.2136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyphyllin D, a steroidal saponin inParis Polyphylla, in growth inhibition of human breast cancer cells and in xenograft

Abstract: Paris polyphylla is a traditional Chinese Medical herb that has been used in treating cancer for thousands of year. Without studies on the anticancer effects of Paris polyphylla being initiated before, we have first studied the component of Paris polyphylla and have spotted out a steroidal saponin, polyphyllin D. As long as the chemical structure and the improved synthesis of polyphyllin D were ascertained, both in vitro to in vivo studies were performed. It was found that treatment of MCF-7 and MDA-MB-231 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 12 publications
(18 reference statements)
3
98
0
Order By: Relevance
“…Interestingly, the extracts of the Paris polyphylla plant, containing polyphyllin D, have been long used in traditional Chinese medicine for cancer treatment [72]. Their CMap analysis indicated that polyphyllin D is a trigger for estrogen receptorinduced apoptosis and mitochondria-mediated apoptotic pathways [73].…”
Section: The L1000cdsmentioning
confidence: 99%
“…Interestingly, the extracts of the Paris polyphylla plant, containing polyphyllin D, have been long used in traditional Chinese medicine for cancer treatment [72]. Their CMap analysis indicated that polyphyllin D is a trigger for estrogen receptorinduced apoptosis and mitochondria-mediated apoptotic pathways [73].…”
Section: The L1000cdsmentioning
confidence: 99%
“…Indeed tumor-specific changes in the mtDNA copy number have been reported in human cancers. 12,[15][16][17][18][19][20] Additionally, mtDNA dimers 21 and mtDNA mutations in mitochondrial genes have been found in patients with leukemia, lung cancer, renal cell carcinoma, hepatocellular carcinoma, breast cancer and ovarian cancer. 2,3,13 Interactions between proteins encoded by mitochondrial and nuclear genomes play critical roles in cellular function.…”
Section: Role Of Mtdna In the Pathogenesis Of Mitochondrial Dysfunctimentioning
confidence: 99%
“…Steroidal saponins of P. polyphylla i.e., Polyphyllin D could serve as an agent for breast cancer treatment (Lee et al, 2005). It was found that treatment of MCF-7 and MDA-MB-231 cells with Polyphyllin D resulted in the inhibition of viability and induction of apoptosis in a dose dependent manner.…”
Section: Phytoconstituents and Pharmacological Activity:-mentioning
confidence: 88%